Conceptual transfer studies in the context of second language acquisition: a scoping review - Xu, Zhaorong; Mamat, Roslina; Mohd Zin, Zaid (Penerbit Universiti Kebangsaan Malaysia, 2024)
Conceptual transfer has emerged as a prominent focus in Second Language Acquisition (SLA) research since1998. Given the complex and diverse theoretical frameworks associated with conceptual transfer, a commitment to methodological rigor within this field becomes imperative. Currently, among the existing review studies pertaining to conceptual transfer, there seems to be a lack of comprehensive studies conducted to discover how this broad topic has been approached in the literature. This scoping review has synthesised empirical studies on conceptual transfer, focusing on publications indexed in the Social Sciences Citation Index and Chinese Social Science Index from 1998 onwards. A total of 55 studies were coded in terms of adopted theories, research lines of inquiry, participant backgrounds, and research design. The primary aim was to identify the range of goals to date and emerging trends for future research. Our analysis has revealed that empirical research in this area encompassed a broad scope of inquiry lines and employed various research designs. However, several gaps in previous studies were identified, including the following: (1) a lack of critical theoretical explanations in their empirical studies; (2) an unbalanced development of lines of inquiry in conceptual transfer studies; (3) a lack of attention to target foreign languages other than English and participants from alternative educational levels; and (4) homogenisation issues in both their data collection and analysis process. These gaps underscored the pressing need for a more comprehensive and multidimensional investigation in the future.